No pain, no gain: nine proposals to improve the future of international arbitration - de la Jara, José María (2017)
The figure of international arbitration is briefly defined as a method of conflict resolution in the international level, alternative to the Administration of Justice, emphasizing its neutrality, speed and confidentiality.This article shows the new challenges faced by arbitrators, in terms of choice, length of process and efficiency in decision making. In addition, it proposes nine solutions to improve arbitration performance and abbreviate the process of taking decisions.